Exploring the link between income inequality, poverty reduction and economic growth: An ASEAN perspective - Amar, Syamsul; Pratama, Ikbar (IJICC, 2020)
The main objective of the current study is to investigate the role of economic growth and income inequality in poverty reduction. In the emerging economies, there are more significant challenges of income inequalities as compared with the vibrant economies. For dealing with the issues of poverty in a successful way, there is a need to tackle the income inequalities. It has been proposed that policies working at redistribution of income should be implemented by the governments to support low-income families. Increase of income inequality is linked with economic growth. For development of economy, high-income inequality is essential as it decreases the advantages of economic growth for poor people. The increasing inequality of income and extensive poverty are major issues in the process of development. The key objective for most of the policies on economic growth is to reduce these issues. The previous research studies have used the traditional measures for income poverty, including index of the poverty gap and a headcount ration. However, the measures of human poverty that have become crucial estimators of social development and living conditions have been used in this research. The study has employed the dynamic panel data approach and used the data of 13 years from the period starting from 2004 to 2017. It has been suggested by the empirical analysis, that poverty levels reduce through economic growth in the emerging world. The levels of income poverty and poverty have a downward trend. It is implied by the results of research that the incomes of the poor should not be the only focus on countries to reduce poverty. Instead, there is a need to improve the provision of necessary facilities and an improvement in life expectancy rates to eliminate the poverty levels.